2003
DOI: 10.1007/s11894-003-0007-9
|View full text |Cite
|
Sign up to set email alerts
|

Current use of transjugular intrahepatic portosystemic shunts

Abstract: The principal indication for transjugular intrahepatic portosystemic shunts (TIPS) continues to be rescue therapy for variceal hemorrhage that cannot be controlled by endoscopic or medical therapy. TIPS provide no survival advantage in prevention of rebleeding or refractory ascites. The indications for TIPS continue to expand, however, especially for Budd-Chiari syndrome and hydrothorax. Other more novel indications include bleeding portal hypertensive gastropathy or ectopic varices, Budd-Chiari syndrome, veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 111 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…In contrast, GAVE does not resolve after lowering portal pressure with TIPS, and GAVE is, therefore, likely related to hepatic dysfunction rather than portal hypertension [78] . TIPS also decreased the risk of PHG bleeding [75][76][77]100,[249][250][251][252][253] . For example, Kamath et al [75] reported TIPS led to improvement or resolution of PHG findings and decreased transfusion requirements from 2.9 ± 2.0 (SD) units/mo of packed erythrocytes before TIPS to 0.6 ± 0.8 units/mo after TIPS performed for severe PHG (P = 0.04).…”
Section: Summary Of Clinical Treatmentmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast, GAVE does not resolve after lowering portal pressure with TIPS, and GAVE is, therefore, likely related to hepatic dysfunction rather than portal hypertension [78] . TIPS also decreased the risk of PHG bleeding [75][76][77]100,[249][250][251][252][253] . For example, Kamath et al [75] reported TIPS led to improvement or resolution of PHG findings and decreased transfusion requirements from 2.9 ± 2.0 (SD) units/mo of packed erythrocytes before TIPS to 0.6 ± 0.8 units/mo after TIPS performed for severe PHG (P = 0.04).…”
Section: Summary Of Clinical Treatmentmentioning
confidence: 89%
“…TIPS reduces the frequency and severity of PHG because it lowers portal pressure [76] . PHG can sometimes resolve completely after TIPS [75][76][77][249][250][251][252][253] . Urata et al [77] reported in a prospective study of 12…”
Section: Summary Of Clinical Treatmentmentioning
confidence: 99%
“…TIPS creation was performed in all patients as previously described [1][2][3][4]15 and included transjugular catheterization of the portal vein. The portal vein was punctured, pressures measured in its main stem and the inferior vena cava above the hepatic veins, the needle track dilated using a balloon catheter, and one to 3 stents (Wallstent; Boston Scientiˆc, Natick, MA, USA) placed.…”
Section: Tipsmentioning
confidence: 99%
“…Recent reports indicate one-year mortality rates between 10z to 54z [1][2][3][4] and 30-day mortality as high as 55z 5 ; various complications after TIPS creation, such as shunt dysfunction and onset or worsening of hepatic encephalopathy, [1][2][3][4] can worsen patient quality of life (QOL); and technical di‹culties in the TIPS procedure diŠer from patient to patient.…”
Section: Introductionmentioning
confidence: 99%